Low complexity uplink multiuser MIMO detecting algorithm - HEI Yong-qiang1; LI Xiao-hui1; YI Ke-chu1; YANG Hong2 (Tongxin xuebao)
Aiming at the uplink multiuser MIMO system,a new space-time detecting algorithm was proposed,in which a linear recombination strategy was imposed on the received signal first,and then the matched filter vectors orthogonal to each users’ interference sets were used to eliminate the interference among users.Finally the signal of each user was line-arly space-time decoded by means of the orthogonal equivalent channel.The design of the algorithm under imperfect channel scenario was also provided.Theory analysis and simulation results reveal that the proposed algorithm has the advantages of low complexity and good robustness,and is superior to other detecting algorithms.